Penggunaan Tanaman Sebagai Obat pada Masyarakatan Suku Banjar, Dayak, dan Bugis di Kalimantan Selatan: The Use of Plants as Medicine in the People of Banjar, Dayak, and Bugis Tribes in South Kalimantan - Melviani Melviani; Rohama Rohama; Noval Noval (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The development of science and technology in the development of pharmaceutical products that are going fast does not make society switch completely to modern medicine; it can be seen from how some of society for generations still utilize the potential of plants for treatment. This research is useful to find out the picture of plants used as medicine in the Banjar Tribe, Dayak Tribe, and Bugis tribe in South Kalimantan. This research method is an observational research design with a cross-sectional approach, using convenience sampling techniques. The results obtained there are 44 types of plants used, with the largest percentage being ginger which serves as body warmth and guava to treat stomach pain (12.0%), betel leaves to reduce body odor (9.0%), turmeric, Dutch jackfruit leaves or soursop leaves and cat whiskers (5.0%), sungkai (4.0%), bay leaves (3.0%) and other plants with a percentage (45%). The type of plant used is herbaceous (40.0%). The largest part of the plant is the leaves (55.0%) processed by boiling (65.0%).